2020
DOI: 10.1177/0269215520946386
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcranial magnetic stimulation on the performance of the activities of daily living and attention function after stroke: a randomized controlled trial

Abstract: Objective: We aimed to interrogate the effects of transcranial magnetic stimulation (TMS) on the performance in activities of daily living (ADL) and attention function after stroke. Design: Randomized controlled trial. Setting: Inpatient rehabilitation hospital. Subjects: We randomized 62 stroke patients with attention dysfunction who were randomly assigned into two groups, and two dropped out from each group. The TMS group ( n = 29) and a sham group ( n = 29), whose mean (SD) was 58.12 (6.72) years. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 34 publications
3
69
0
Order By: Relevance
“…The reason for choosing DLPFC was that all studies indicated that DLPFC was an important site in cognitive function. Some studies have shown that DLPFC is associated with WM [32,36,40], is an important part of the Default mode network [33], is a hub of attentional function [32], and plays an important part in the central executive network (CEN), which is responsible for high-level cognitive functions such as control of attention and WM [34]. Except for the study by Hosseinzadeh et al [41], excitatory stimulation of the frontal lobe was selected in tDCS studies [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason for choosing DLPFC was that all studies indicated that DLPFC was an important site in cognitive function. Some studies have shown that DLPFC is associated with WM [32,36,40], is an important part of the Default mode network [33], is a hub of attentional function [32], and plays an important part in the central executive network (CEN), which is responsible for high-level cognitive functions such as control of attention and WM [34]. Except for the study by Hosseinzadeh et al [41], excitatory stimulation of the frontal lobe was selected in tDCS studies [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, all patients received rehabilitation regardless of the intervention group or control group. In rTMS, five studies combined cognitive rehabilitation and cognitive training [32][33][34][35][36]. Yin et al [34] and Lu et al [35] combined computer-assisted cognitive training in all patients [34,35].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcranial magnetic stimulation is a non-invasive and painless form of therapy, widely used in the neurorehabilitation in post-stroke patients [100][101][102]104]. TMS is based on generating a magnetic pulse that induces power in various regions of the cerebral cortex.…”
Section: Transcranial Magnetic Stimulation (Tms)mentioning
confidence: 99%
“…rTMS is a non-invasive and relatively safe technique that has been used in cognition impairment (Fisicaro et al, 2019). Several studies have shown the efficacy of TMS in improving cognition function in patients with PSCI (Liu et al, 2020;Tsai et al, 2020). They found that rTMS can improve attention, memory, executive and overall cognitive function after stroke (Hara et al, 2021).…”
Section: Optimization Of Rtms For Cortical Fc Patternmentioning
confidence: 99%